Reflecting on psychotherapy and subjective well-being (in) ability to regulate the basic psychological needs - Vaz-Velho, Catarina (2011)
With the aim of Well-Being, psychotherapeutic work on the fundamental psychological needs, can be seen as a more or less explicit objective of psychotherapy. The concept of psychological needs and attempted explanation of basic psychological needs have been made in various psychotherapeutic models (e.g. Benjamin, 2003; Blatt, 2008; Young, Klosko & Weishaar, 2003) and other psychological models (e.g. Deci & Ryan, 2000; Epstein, 1993; Maslow, 1954; Sheldon, Elliot, Kim & Kasser, 2001). In this theoretical presentation, we briefly discuss the history of the construct of basic psychological needs, and discuss some of these models, trying to clarify how the psychotherapeutic processes can facilitate, or hinder, the flexible regulation of the different psychological needs and thus, adaptation and Subjective Well-Being.